PENDIDIKAN BERBASIS KONSTRUKTIVISME DALAM MENINGKATKAN KEBERMAKNAAN BELAJAR DI ERA DIGITAL - Zahrotus Saidah (Wahana Islamika: Jurnal Studi Keislaman, 2021)
Substantive meaningfulness is defined by theability of students to be associated with relevant conceptscontained in students' cognitive learning, resulting in funlearning, so that it can be achieved, and expressinginformation in its entirety, as well as having implications forincreasing students' abilities in constructing new knowledge,thus producing results. The research aims to answer how theimpact of implementing constructivism-based learning in thedigital era questions in increasing the meaning of PAIlearning to produce digitally. This is a qualitative study thattakes a case study approach. The key sources used weredocumentation, in-depth interviews, and focus groupdiscussions with students from SD Muhammadiyah 1Alternative Magelang. Books, papers, journals, magazines,articles, journals, websites, and other secondary sourcesrelating to the study issue are utilized. According to thestudy's findings, learning is the key to student empowermentin the technological environment. This study shows thatusing digital-based constructivist learning approaches, themeaning of Islamic Religious Education learning for thetechnical background can be increased